2013
DOI: 10.1080/13548506.2013.802357
|View full text |Cite
|
Sign up to set email alerts
|

Depression and cardiac symptoms among AL amyloidosis patients: the mediating role of coping strategies

Abstract: As cardiac symptoms have low severity, AL patients can avoid the disease. However, as cardiac symptoms proceed and interfere with daily activities, they can no longer ignore their signs thus perceiving the severity of their medical condition. This status makes individuals prone to seek less social support and thus to prefer social isolation. Results suggest the need for early psychological support on coping strategies for AL cardiologic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…This re ects existing grey literature such as a survey of UK-and US-based respondents which reported high levels of 'worry,' 'anxiety and stress' and 'depression' amongst rare disease patients and carers [1] and a Europe-wide survey that found 38% of respondents felt they needed psychological support [28]. It is also consistent with ndings from condition-speci c studies which used diagnostic tools to measure anxiety and/or depression in rare disease patients and/or carers [18,19,20] and impact on quality of life [15,16,17].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This re ects existing grey literature such as a survey of UK-and US-based respondents which reported high levels of 'worry,' 'anxiety and stress' and 'depression' amongst rare disease patients and carers [1] and a Europe-wide survey that found 38% of respondents felt they needed psychological support [28]. It is also consistent with ndings from condition-speci c studies which used diagnostic tools to measure anxiety and/or depression in rare disease patients and/or carers [18,19,20] and impact on quality of life [15,16,17].…”
Section: Discussionsupporting
confidence: 58%
“…These studies have generally indicated considerable impairment on quality of life for rare disease patients, including individuals with oculopharyngeal muscular dystrophy [15], and epidermolysis bullosa [16]; and also parents and carers of individuals with epidermolysis bullosa [16] and CDKL5 disorder [17]. A number of groups have also applied validated tools to screen for depression and/or anxiety amongst rare disease patients, including individuals with myocarditis [18], AL amyloidosis [19] and mitochondrial disorders [20], and have typically reported signi cant mental health impairments. Additionally, a recent German cross-sectional study reported increased levels of depression and anxiety in a mixed rare disease cohort [21].…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with this hypothesis, it has already been demonstrated that ATTRm and ATTRwt amyloidosis have better prognoses, despite patients' older age at diagnosis and echocardiographic evidence of thicker ventricles, with an overall survival at 2 years of 63% for AL, 98% for ATTRm, and 100% for ATTRwt …”
Section: Discussionmentioning
confidence: 61%
“…The ATTR form can be further classified in hereditary transthyretin‐related amyloidosis (ATTRm), due to mutations in the gene codifying for transthyretin, and systemic senile amyloidosis, a noninherited form caused by the deposition of the wild‐type transthyretin (TTR) protein (ATTRwt) in the extracellular space . Cardiac involvement is frequent in both AL and ATTR amyloidosis, and is associated with important clinical and psychological consequences that have a significant impact on prognosis…”
Section: Introductionmentioning
confidence: 99%
“…Symptom-related coping may mediate the relationship between daily physical symptoms and mood changes, based on the transactional stress-coping theory (Lazarus & Folkman, 1984). Some studies have already investigated this issue (Barakat et al, 2007;Smorti et al, 2014), however, not in the context of everyday life or specific variability of individuals. Although Gruszczyńska and Knoll (2015) investigated lower-level mediating effect of meaning-focused coping in association with pain and PA, dynamic compounds between these variables were not tested (only the same-day associations were analyzed).…”
Section: Introductionmentioning
confidence: 99%